THE ROLE OF CONTEMPORARY LEADERSHIP AT THE LIBRARY AND INFORMATION SCIENCE STUDENT ASSOCIATION IN THE FACULTY OF HUMANITIES, UNIVERSITAS INDONESIA - Zaidan Abdurrahman Qois; Rahmi Rahmi (Journal of Leadership in Organizations, 2021)
Introduction/Main Objectives: Leadership is important in enabling a person and a nation to improve and advance.  Background Problems: Leadership is not something that everyone seeks, especially in youth. The youth leadership crisis can be seen from the lack of students who want to become chairpersons in university extracurricular activities. Novelty: This research makes a three-fold contribution. First, this study presents an analysis of the ‘Evolving Leadership Practices Assessment’ quizzes (Olson and Singer, 2004) distributed by the Chairperson and Vice-chairperson of the Library Science Student Association (IMASIP) the Faculty of Humanities, Universitas Indonesia. Second, this study assesses the IMASIP FIB-UI Daily Management Board. This study also interviewed five informants with 12 closed-ended questions. Research Methods: This paper assesses youth leadership by using a mix of qualitative and quantitative methods, with a case study approach.  Finding/Results: Our result shows and supports the assumption that age and years of leadership will affect the scores obtained at IMASIP, which further research must examine. This research also suggests that the Daily Management Board's performance can be maintained by connection, contribution, and collaboration. Conclusion: The results identify efforts to build and improve leadership among students, including developing and increasing seminars and training in leadership to prepare students who have a role as the successors of the nation’s leadership.